Elder parent health and the migration decision of adult children: evidence from rural China - John Giles; Ren Mu (Institute for the Study of Labor (IZA), 2006)
Recent research has shown that participation in migrant labor markets has led to substantial increases in income for families in rural China. This paper asks how participation is affected by elder parent health. We find that younger adults are less likely to work as migrants when a parent is ill. Poor elder parent health has less impact on the probability of employment as a migrant when an adult child has siblings who may be available to provide care. We also highlight the potential importance of including information on non-resident family members when studying how parent illness and elder care requirements influence the labor supply decisions of adult children.
urn:nbn:de:101:1-20090825270
Keywords: 330; Binnenwanderung; Gesundheit; Eltern; China